Conflict Resolution and its Implications: An Organisational Paradigm - Ugorji, Rex Uzor; Ugwu, Callistus Chinwuba; Okojie, J O (Practicum Psychologia, 2018)
The notion of conflict and its resolution both within the paradigms of the wider society and the narrow confines of the organisation are examined in the light of current thinking. An expose of the consequences and/or implications of this discourse is presented. The paper proposes that positionally, a conflict and a disagreement in general terms, are synonyms rather than antonyms; and that they are a sine qua non of human behaviour. From conceptual and methodological standpoints, two main dimensions underlying the intentions of the groups involved in a conflict situation are isolated. Finally, these two main dimensions ultimately produce five conflict-handling modes in organisations; and these modes are discussed contemporaneously.